High-sensitivity detection of ethane and ethylene using gamma-irradiated ZnO chemiresistors. (December 2022) - Aldosary, Abdullah F; Shar, Muhammad Ali; AlQahtani, Hadi Rasam
Abstract: Gamma irradiated ZnO chemical sensors showed highly sensitive and selective responses to 1.2 ppm of ethane and ethylene. Scanning electron microscopy images showed the formation of nanosized features on the surface of ZnO after irradiation. The porosity, crystallite size, and points defects (mainly oxygen and zinc vacancies) of the studied ZnO thin films were found to increase with increase in gamma irradiation. The sensitivity of ZnO chemical sensors increased with increase in the radiation dose. The ZnO sensors exhibited approximately 440 and 730% enhancements in the sensitivity to ethane and ethylene, respectively after irradiation with 200 kGy. The sensitivity and selectivity of the ZnO sensors to ethane and ethylene were interpreted from the radiation-induced changes in surface morphology that led to higher surface area and changes in surface chemistry with abundance of oxygen and zinc vacancies.